Clinical and laboratorial correlation of postoperative hypocalcemia after extensive thyroidectomy - Gonçalves, Antonio José; Martins, Laércio; Souza, Tania Regina Bastos de; Alves, Paulo Jorge Correia; Schiola, Alexandre; Rios, Oswaldo Angel Bellido; Santos, Adriana Ribeiro dos (São Paulo Medical Journal, 1997)
The medical records of 84 patients submitted to extensive thyroidectomy from January 1991 to April 1995 were reviewed and the data was analyzed in order to verify a correlation between postoperative laboratories results and physical findings suggestive of hypocalcemia. It was verified that there was hypocalcemia in 51.2 percent of the patients, of which only 18.6 percent presented symptoms. It was concluded that asymptomatic hypocalcemia is frequent in extensive thyroidectomy and a routine screening for serum calcium in the postoperative period following thyroidectomy and calcium reposition must be systematic.